DEVELOPMENT OF COMPONENTS OF MUSICAL RHYTHMIC MOVEMENTS IN FUTURE MUSIC TEACHERS BASED ON A PEDAGOGICAL APPROACH - Shodieva Oh Yigul (American Journals, 2023)
The article discusses the development society and quality education as more relevant my problem in everyone world today than ever and decision such question requires carrying out complex reforms in the system education and creation modern systems training.
Keywords: musical-rhythmic movements, musical-rhythmic competencies, harmony of music and movement, musical works, musical hearing, memory, attention, feeling rhythm, plastic expressive movement.